POLA PENYEBARAN (Nepenthes spp.) DI GUNUNG ROREKAUTIMBU KAWASAN TAMAN NASIONAL LORE LINDU - Khalid, Idham; Mallombasang, Sri Ningsih; Irmasari, Irmasari (Jurnal Warta Rimba, 2015)
Nepenthes spp. is a species of vegetation lives in nature and known to be currently threatened. The species is unique for being the prey of insects. The lack of information regarding its distribution on Lore Lindu National Park (LLNP) lead this research to study such the issue. The research aims to study the distribution of the species living within the park particularly on the Rorekautimbu Mount. The results of the research is expected to enrich information regarding flora and fauna database to improve conservation program lead by the LLNP. The research was conducted from March – May 2014 located on trekking lane of The Rorekautimbu Mount. Purposive sampling method was applied during the research. Data regarding coordinate, elevation and the number of individuals were collected through direct observation using transect of 10 m x 10 m each plot. During the research, three species of nepenthes were found. They were N. maxima Rein. ex Nees, N. tentaculata Hook.f., and N. pitopangii Lee. They were identified at the elevation of 1,800 – 2,330 MSL and contagiously distributed based on Morisita Index (Iδ) with Ip > 0. The distribution pattern of the three species listed above can be described as, respecively, Ip > 0.5526, Ip > 0.4846, and Ip > 0.4267. Keywords: distribution pattern, Nepenthes, Lore Lindu National Park